A facile route to the production of polymeric nanofibrous aerogels for environmentally sustainable applications. Issue 8 (8th February 2018) - Liu, Qiongzhen; Chen, Jiahui; Mei, Tao; He, Xiaowei; Zhong, Weibing; Liu, Ke; Wang, Wenwen; Wang, Yuedan; Li, Mufang; Wang, Dong
Abstract : The elastic nanofibrous aerogels can be facilely fabricated employing PVA- co -PE nanofibers suspension and demonstrate excellent candidates for environmentally sustainable applications. Abstract : Mesoporous polymeric aerogels with high compressibility and durability have attracted great attention due to their environmentally sustainable applications. However, it is still challenging to develop polymeric aerogels in a simple, low-cost and mass produced way. Herein, we report a strategy to prepare a high porosity polymeric nanofibrous aerogel (referred to as NFA) by direct freeze-drying of the poly(vinyl alcohol- co -ethylene) (PVA- co -PE) nanofibrous suspension. It is noteworthy that this process is free of gelation and any solvent exchange. In addition, the PVA- co -PE nanofibers were mass-produced from our production line, based on a high throughput Melt-Extrusion-Phase-Separation technique. Additionally, the network of the NFA aerogels can be tuned by the host–guest assembly of the nanofibers and the foreign PVA nano-lamellae from disordered/ordered cellular to a leaf-like structure. Further modification of the NFA by gaseous methyltrichlorosilane (MTS) led to covalently bonded siloxane nanoparticles formed on the surface, thereby facilely realizing the nanofibrous aerogel from hydrophilic to hydrophobic as well as achieving excellent resilience. The corresponding hydrophobic aerogel (designated as HNFA) possessed a slightly larger density of 11.1 mg cm −3 with an almost unchanged porosity of 99% and meso–macroporous pores of 5–100 nm compared with the NFA (8.3 mg cm −3 ). They are demonstrated as good thermal insulators (0.033–0.044 W m −1 K −1 ), high-performance air filters (99.2% filtration efficiency with 64 Pa pressure drop), organic pollutants absorbers (2500–5329% weight gain) and continuous water/oil separators. Therefore, this study opens up a new approach for simple and large-scale preparation of polymeric aerogels for versatile applications.